Transforming food systems under climate change: Local to global policy as a catalyst for change - Rawe, Tonya; Antonelli, Marta; Chatrchyan, Allison M.; Clayton, Terry; Fanzo, Jessica; Gonsalves, Julian Francis; Matthews, Alan; Nierenberg, Danielle; Zurek, Monika (2019)
Feeding and nourishing a growing and changing global population in the face of rising numbers of chronically hungry people, slow progress on malnutrition, environmental degradation, systemic inequality, and the dire projections of climate change, demands a transformation in global food systems. Policy change at multiple levels is critical for catalysing an inclusive and sustainable transformation in food systems; global and regional policy are transformative only insofar as they are translated into ambitious national action with adequate support, including both public and private investment. Three areas of policy change show potential to be catalytic: 1) reducing emissions and increasing resilience, 2) tackling food loss and waste, and 3) shifting diets to promote nutrition and sustainability. Trade-offs mean a multi-sectoral approach to policymaking is needed, while inequalities in food systems necessitate transparent, inclusive processes and results. Gender inequality, in particular, must be addressed. Transformation demands participation and action from all actors.